An investigation of coupling mechanisms in narrowband microwave filters - Hansmann, Esti Mari (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2008.